Odpowiedź :
a) 4x - 3 + 5x = 15
9x - 3 = 15
9x = 15 +3
9x = 18
x = 2
b) 5x + 7 - 3x = 13
2x + 7 = 13
2x = 6
x = 3
c) 7x - 2 - 6x = 5
x - 2 = 5
x = 5 + 2
x = 7
d) 6x - 4 + 4x = 56
10x - 4 = 56
10x = 56 + 4
10x = 60
x = 6
e) 2x - 3 + x = 9
3x - 3 = 9
3x = 9 + 3
3x = 12
x = 4
f) 3x - 5 - x = 11
2x - 5 = 11
2x = 11 + 5
2x = 16
x = 8
g) x - 5 + 6x = 16
7x - 5 = 16
7x = 16 + 5
7x = 21
x = 3
h) 3x - 4 - 2x = 16
x - 4 = 16
x = 16 + 4
x = 20
Odpowiedź:
a)4x-3+5x=15
4x+5x=15+3
9x=18/9
x=2
b)5x+7-3x=13
5x-3x=13-7
2x=6/2
x=3
c)7x-2-6x=5
7x-6x=5+2
x=7
d)6x-4+4x=56
6x+4x=56+4
10x=60/10
x=6
e)2x-3+x=9
2x+x=9+3
3x=12/3
x=4
f)3x-5-x=11
3x-x=11+5
2x=16/2
x=8
g)x-5+6x=16
x+6x=16+5
7x=21/7
x=3
h)3x-4-2x=16
x=16+4
x=20
Szczegółowe wyjaśnienie:
Myślę, że pomogłam wszytko powinno być dobrze:)